2016
DOI: 10.1016/j.vaccine.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies derived from an enterotoxigenic Escherichia coli (ETEC) adhesin tip MEFA (multiepitope fusion antigen) against adherence of nine ETEC adhesins: CFA/I, CS1, CS2, CS3, CS4, CS5, CS6, CS21 and EtpA

Abstract: Diarrhea continues to be a leading cause of death in children younger than 5 years in developing countries. Enterotoxigenic Escherichia coli (ETEC) is a leading bacterial cause of children’s diarrhea and travelers’ diarrhea. ETEC bacteria initiate diarrheal disease by attaching to host receptors at epithelial cells and colonizing in small intestine. Therefore, preventing ETEC attachment has been considered the first line of defense against ETEC diarrhea. However, developing vaccines effectively against ETEC ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Recombinant CfaB-epitope (CfaB-FedF-ep) fusion proteins expressed by E. coli BL21 (DE3) were extracted with bacterial protein extraction reagent (B-PER; Thermo Fisher Scientific, Rochester, NY) and refolded as we previously described (Huang et al, 2018;Nandre et al, 2016;Rausch et al, 2017). Refolded fusion proteins were examined in SDS-PAGE with Coomassie blue staining, and were characterized in Western blot or direct ELISAs with anti-F18 mouse antiserum.…”
Section: Cfab-epitope Fusion Protein Expression and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant CfaB-epitope (CfaB-FedF-ep) fusion proteins expressed by E. coli BL21 (DE3) were extracted with bacterial protein extraction reagent (B-PER; Thermo Fisher Scientific, Rochester, NY) and refolded as we previously described (Huang et al, 2018;Nandre et al, 2016;Rausch et al, 2017). Refolded fusion proteins were examined in SDS-PAGE with Coomassie blue staining, and were characterized in Western blot or direct ELISAs with anti-F18 mouse antiserum.…”
Section: Cfab-epitope Fusion Protein Expression and Characterizationmentioning
confidence: 99%
“…Blocking attachment of all ETEC fimbriae and neutralizing against enterotoxicity of LT and STs have proven very challenging. However, a recent breakthrough in antigen preparation by using neutralizing epitopes and multiepitope-fusion-antigen (MEFA) technology makes completion of such a task feasible Nandre et al, 2016Ruan et al, 2014a. Additionally, molecular epidemiological studies showed that the vast majority of ETEC strains causing PWD express K88 or F18 fimbriae in conjunction with 2-3 toxins (Frydendahl, 2002;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids (pET28␣) carrying the chimeric adhesin-toxoid MEFA gene were introduced into E. coli BL21 bacteria to express tagless adhesin-toxoid MEFA protein. Protein expression, extraction, and refolding followed protocols described previously (37,38). Briefly, a single colony of the recombinant strain was cultured in 5 ml lysogeny broth (LB) supplemented with kanamycin (30 g/ml) at 37°C on a shaker (150 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…55 Accordingly, in silico predicted B-cell epitopes from CFA/I, CS1, CS2, CS3, CS4, CS5, CS6, CS21, and EtpA were inserted into the backbone of the colonization factor antigen I (CFA/I) tip subunit CfaE where they replaced surface exposed, but less antigenic peptides. 56 Notably, mice immunized with the chimeric antigen elicited antibodies against all the nine epitopes, and the sera prevented the attachment of ETEC strains to Caco-2 cells in vitro. 56 MEFA CFs were further genetically fused to an ST toxoid and LT antigen to afford even broader protection.…”
Section: Recent Updates On Cf-based Etec Subunit Vaccine Developmentmentioning
confidence: 96%
“…56 Notably, mice immunized with the chimeric antigen elicited antibodies against all the nine epitopes, and the sera prevented the attachment of ETEC strains to Caco-2 cells in vitro. 56 MEFA CFs were further genetically fused to an ST toxoid and LT antigen to afford even broader protection. 57,58 Immunized mice that were challenged with lethal doses of ETEC (CFA/I + , LT + , ST + ) were protected.…”
Section: Recent Updates On Cf-based Etec Subunit Vaccine Developmentmentioning
confidence: 96%